Impact of curing conditions for concrete on its mechanical properties - Witkowska-Dobrev, Joanna; Szlachetka, Olga; Spiek, Paulina (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
This paper aims to present the results of compressive strength tests of concrete specimens, prepared according to two recipes, after 2, 7 and 28 days of maturing in four different environments. The concrete specimens had the same w/c ratio, the same amount of aggregate of particular fractions, the addition of a superplasticizer, but they differed in the cement type. In one recipe, the Portland cement CEM I 32.5R was used, in the other – pozzolanic ash cement CEM IV/B(V) 32.5R-LH/NA. Concrete specimens with dimensions of 100 x 100 x 100 mm made according to both recipes were placed in individual ripening environments: in cuvettes with water, soaked and wrapped with construction foil, left in room conditions in the laboratory, placed outside the laboratory and being exposed to the atmospheric conditions. The obtained compressive strength results confirmed that the best way of curing concrete is the wet cure (in cuvettes with water). It has been proven that the choice of proper curing method is key in terms of compressive strength.